2014
DOI: 10.1108/ijmhsc-07-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

A narrative literature review on the health of migrant farm worker children in the USA

Abstract: Purpose – The purpose of this paper is to provide a comprehensive narrative review of the literature on migrant farm worker child and adolescent health. It highlights current health issues and suggests methods to improve research and clinical practices with this underserved and vulnerable population. Design/methodology/approach – The methodology for this narrative review included a search of articles published between 2000 and 2012. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Overall, we found few high-quality evaluation research papers. A large proportion of existing studies are conceptual and descriptive, with a limited focus on specific migrant issues, populations, or settings (Barrie & Mendes, 2011;Botfield et al, 2016;Connor et al, 2014;Demazure et al, 2018;Ehntholt & Yule, 2006;Nocon et al, 2017;Streitwieser et al, 2018;Sullivan & Simonson, 2016;Tyrer & Fazel, 2014;Vossoughi et al, 2018). Also, the studies reviewed did not explicitly report any collaborative co-designed activities with communities, institutions and services including young migrants and refugees that are affected by the programmes offered (Graham, Kothari, & McCutcheon, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we found few high-quality evaluation research papers. A large proportion of existing studies are conceptual and descriptive, with a limited focus on specific migrant issues, populations, or settings (Barrie & Mendes, 2011;Botfield et al, 2016;Connor et al, 2014;Demazure et al, 2018;Ehntholt & Yule, 2006;Nocon et al, 2017;Streitwieser et al, 2018;Sullivan & Simonson, 2016;Tyrer & Fazel, 2014;Vossoughi et al, 2018). Also, the studies reviewed did not explicitly report any collaborative co-designed activities with communities, institutions and services including young migrants and refugees that are affected by the programmes offered (Graham, Kothari, & McCutcheon, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on the existing literature, a new synthesis of current evidence-based wellbeing promotion approaches for young migrants and refugees is warranted for a few reasons. Firstly, a large proportion of existing reviews are conceptual and descriptive, with a limited focus to specific migrant issues, populations, or settings (Barrie & Mendes, 2011;Botfield, Newman, & Zwi, 2016;Connor, Page Layne, & Ellis Hilb, 2014;Demazure, Gaultier, & Pinsault, 2018;Ehntholt & Yule, 2006;Nocon, Eberle-Sejari, Unterhitzenberger, & Rosner, 2017;Streitwieser, Loo, Ohorodnik, & Jeong, 2018;Sullivan & Simonson, 2016;Tyrer & Fazel, 2014;Vossoughi, Jackson, Gusler, & Stone, 2018). Secondly, there are insufficient numbers of rigorously designed and executed systematic reviews that also include a transparently reported study quality appraisal (Borsch et al, 2018;Botfield, Newman, Lenette, Albury, & Zwi, 2018;d'Abreu, Castro-Olivo, & Ura, 2019;Nakeyar, Esses, & Reid, 2018;Van Os, Zijlstra, Knorth, Post, & Kalverboer, 2018).…”
mentioning
confidence: 99%
“…This review is warranted for at least two reasons. Firstly, a large proportion of existing reviews are conceptual and descriptive, with a focus limited to specific migrant issues, populations, or settings (Barrie & Mendes, 2011; Botfield et al, 2016; Connor et al, 2014; Demazure et al, 2018; Ehntholt & Yule, 2006; Nocon et al, 2017; Streitwieser et al, 2019; Sullivan & Simonson, 2016; Tyrer & Fazel, 2014; Vossoughi et al, 2018). Secondly, there are few rigorously designed and executed systematic reviews that include a transparently reported study quality appraisal (Borsch et al, 2019; Botfield et al, 2018; D’Abreu et al, 2019; Nakeyar et al, 2018; van Os et al, 2018).…”
Section: Introductionmentioning
confidence: 99%